2017
DOI: 10.1186/s13054-017-1757-3
|View full text |Cite
|
Sign up to set email alerts
|

The common promoter polymorphism rs11666254 downregulates FPR2/ALX expression and increases risk of sepsis in patients with severe trauma

Abstract: BackgroundFormyl peptide receptor 2-lipoxin receptor (FPR2/ALX) modulates the anti-inflammatory response and therefore may be a target for treating sepsis. The purpose of this study was to investigate the association between genetic variants of the FPR2/ALX gene and sepsis after severe trauma as well as to further analyze the functions of sepsis-related genetic polymorphisms.MethodsThree tag single-nucleotide polymorphisms (tag SNPs) that captured all common alleles across the FPR2/ALX genomic region were geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Most available studies use the candidate gene approach dealing with, for example, cytokine genes that can affect the inflammatory response, genes encoding for patternrecognition receptors (like Toll-like receptors), or genes that shape the response to infections. 14,15 As such studies often suffer from poor reproducibility, an alternative could be conducting well planned and well powered data-driven genomic studies. Typically, these works are developed in consortia and lead to highly reproducible associations.…”
Section: The Role Of Neutrophils and Nets In Sepsismentioning
confidence: 99%
“…Most available studies use the candidate gene approach dealing with, for example, cytokine genes that can affect the inflammatory response, genes encoding for patternrecognition receptors (like Toll-like receptors), or genes that shape the response to infections. 14,15 As such studies often suffer from poor reproducibility, an alternative could be conducting well planned and well powered data-driven genomic studies. Typically, these works are developed in consortia and lead to highly reproducible associations.…”
Section: The Role Of Neutrophils and Nets In Sepsismentioning
confidence: 99%
“…Thus, studies that assess the presence of these receptors in the T cells of TT/BT and BL/LL patients are required to fully understand the potential influence of RvD1 on the adaptive immune response across the spectrum of leprosy. Polymorphisms in the promoter region of the ALX/FPR2 gene resulting in a reduced expression of this receptor are known ( 100 , 101 ). Thus, it would also be interesting to investigate whether polymorphisms exist between TT/BT and BL/LL patients in the promoter or functional regions of the GPR32 and ALX/FPR2 genes.…”
Section: The Specialized Pro-resolving Rvd1 In Leprosy: Bad With It mentioning
confidence: 99%
“…In addition, in vitro studies showed that ALX/FPR2 is a promiscuous receptor that is also recognized and stimulated by a variety of natural and synthetic peptides to translate effects ranging from pro-inflammatory to anti-inflammatory and pro-resolution depending on the activating ligand (reviewed in [79]). However, the ALX/FPR2 transgenic and knock-out mouse models confirmed the crucial role of this receptor in inflammation resolution [80,81], and findings in human indicated that ALX/FPR2 levels dictate the amplitude of inflammation and its defective expression could be associated with inflammatory disorders [82,83].…”
Section: Spm Receptors and Functions In Resolution Of Inflammationmentioning
confidence: 93%